2021 16th International Conference on Design &Amp; Technology of Integrated Systems in Nanoscale Era (DTIS) 2021
DOI: 10.1109/dtis53253.2021.9505101
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Defect Analysis of 8T SRAM Cells for In-Memory Computing Architectures

Abstract: In-Memory-Computing (IMC) paradigm has been proposed as an alternative to overcome the memory wall faced by conventional von Neumann computing architectures. IMC architectures proposed today are built either from volatile or non-volatile basic memory cells, but a common feature is that all of them are prone to manufacturing defects in the same way as conventional memories. In this paper, we propose to analyze the behavior of an IMC 8T SRAM cell in presence of defects located in the read port of the cell. A mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The March C-test algorithm is the following {⇕ (w0); ⇑ (r0, w1); ⇑ (r1, w0); ⇓ (r0, w1); ⇓ (r1, w0); ⇕ (r0)} and has a complexity of 10N (N being the number of cells). It provides a 100% coverage of Stuck-at-Faults (SAF), Transition Faults (TF), idempotent and inversion Coupling Faults (CFid, CFin) and Address decoder Faults (AF), but does not cover all the resistive-short defects located in the read port of the IMC 8T SRAM cells [19]. In summary, functional tests and test algorithms already developed for conventionnel 6T SRAMs testing were used to test 8T SRAM-based computing architectures in memory mode in [17][18].…”
Section: Figure 2 Considered 128x128 Matrix Model With Layout Extract...mentioning
confidence: 99%
See 1 more Smart Citation
“…The March C-test algorithm is the following {⇕ (w0); ⇑ (r0, w1); ⇑ (r1, w0); ⇓ (r0, w1); ⇓ (r1, w0); ⇕ (r0)} and has a complexity of 10N (N being the number of cells). It provides a 100% coverage of Stuck-at-Faults (SAF), Transition Faults (TF), idempotent and inversion Coupling Faults (CFid, CFin) and Address decoder Faults (AF), but does not cover all the resistive-short defects located in the read port of the IMC 8T SRAM cells [19]. In summary, functional tests and test algorithms already developed for conventionnel 6T SRAMs testing were used to test 8T SRAM-based computing architectures in memory mode in [17][18].…”
Section: Figure 2 Considered 128x128 Matrix Model With Layout Extract...mentioning
confidence: 99%
“…These solutions mainly consist in modifying March test algorithms through the addition of computing operations. However, as shown by preliminary results presented in [19], these tests do not cover all potential defects that can occur in the IMC architecture. In particular, defects in the memory read port are not covered.…”
Section: Introductionmentioning
confidence: 97%
“…These solutions mainly consist in adding computing operations to the original March test algorithm. As shown in [7], these tests however do not cover all potential defects in the targeted IMC architecture. In particular, defects in the memory read port are not covered.…”
Section: Introductionmentioning
confidence: 99%
“…There is only a limited work published on testing of CIM. Several researchers have studied the impact of resistive defects (e.g., an open connection, or a short-circuit to GND) on the performance of a CIM architecture and subsequently developed tests to detect such modeled defects [4,[10][11][12][13]. The work has shown that there are unique computation faults that are not seen in regular memories.…”
Section: Introductionmentioning
confidence: 99%